REPRODUCTIVE PERFORMANCE OF WILD STRAINS OF Clarias gariepinus BROODSTOCKS FROM NORTH-EAST NIGERIA - Eze, Felix (Jakarta Technical University of Fisheries, 2024)
Fish seed production of Clarias gariepinus has been successfully been carried out in Nigeria. Despite the success, most of the strains used in aquaculture have suffered from inbreeding and its consequences and there still exist a wide gap between fish seed demand and supply, this therefore necessitate the need to increase research. This study focused on intra-specific hybridization among and between wild Clarias gariepinus from four different lakes viz., lake Alau in Borno state, lake Dadin Kowa in Gombe state, lake Maladumba in Bauchi state and lake Mayo Ranewo in Taraba state in the North-East of Nigeria in other to evaluate their reproductive performances. Twenty pairs of live wild gravid broodstocks of C. gariepinus with a mean total length of 47.9±1.08cm and a mean total weight of 951.75±16.55g were randomly collected from each lake. The fish were conditioned, fed and spawned in the Hatchery complex, Department of Fisheries, University of Maiduguri, Nigeria. The broodstocks were mated in pure parental and reciprocal crosses generating sixteen mating combinations (generic crosses) duplicated in complete blocked randomized design. Reproductive performance parameters such as fecundity, fertilization rate, hatching rate, and survival were monitored and the data collected were analyzed using Analysis of Variance (ANOVA) at p<0.05 significant level. The result revealed that the mean highest fecundity (66208±120.12g) was recorded for female broodstocks collected from Lake Mayo Ranewo in Taraba state, crosses between Bauchi♀ and Taraba♂ had the highest values of fertilization rate (95.50±9.50%), hatching rate (93.28±2.00%) and survival rate (88.16±2.50%). Results clearly indicated that reproductive performances varied significantly among and between the pure lines and their reciprocal crosses. Water quality parameters including ammonia (mg/L), pH, water temperature (°C) and dissolved oxygen (mg/L) fell within the recommended range for the culture of fresh water fish. For better reproductive performance of wild strains of Clarias gariepinus, in the North-East of Nigeria, crosses should be encouraged between broodstocks from Bauchi and Taraba.